Employment and Industrialization: Reply - Baer, Werner; Herve, Michel E. A. (Quarterly Journal of Economics, 1967)
Werner Baer, Michel E. A. Hervé; Employment and Industrialization: Reply, The Quarterly Journal of Economics, Volume 81, Issue 3, 1 August 1967, Pages 532–